Recent Semen Exposure Impacts the Cytokine Response and Bacterial Vaginosis in Women - Mngomezulu, Khanyisile; Mzobe, Gugulethu F.; Mtshali, Andile; Osman, Farzana; Liebenberg, Lenine J. P.; Garrett, Nigel; Singh, Ravesh; Rompalo, Anne; Mindel, Adrian; Karim, Salim S. Abdool; Karim, Quarraisha Abdool; Baxter, Cheryl; et al. (Frontiers in Immunology, 2021)
Background: The presence of semen in the vagina from unprotected sex may influence the immune and microbial environment of the female genital tract. Inflammatory cytokine concentrations and BV-associated bacteria in female genital secretions may influence HIV risk, although the effect of recent sexual intercourse on incident BV and the cytokine milieu of cervicovaginal secretions has rarely been measured in previous studies. Here, we investigated the extent to which partner semen impacts the cytokine response and incident BV. Methods: At baseline, we assessed the recency of semen exposure in menstrual cup supernatants by quantifying prostate specific antigen (PSA) levels using ELISA in 248 HIV-uninfected women at high risk for HIV infection. Luminex was used to measure 48 cytokines in menstrual cup supernatants and vaginal swabs to diagnose BV by Nugent score. Point-of-care screening for Chlamydia trachomatis and Neisseria gonorrhoeae was conducted using GeneXpert while OSOM was used for Trichomonas vaginalis detection. Multivariable models, adjusted for age, sexually transmitted infections, BV, current contraception use and condom use, were used to assess the impact of semen exposure on biomarkers of inflammation and BV. Results: Presence of PSA, indicating recent semen exposure within 48 hours prior to sampling, was observed in menstrual cup supernatants of 17% (43/248) of women. Of these women, 70% (30/43) had self-reported condom use at their last sex act and 84% (36/43) had BV (Nugent score >7). PSA presence was significantly associated with prevalent BV (Relative Risk (RR), 2.609; 95% Confidence Interval (CI), 1.104 - 6.165; p = 0.029). Furthermore, women with detectable PSA had high median concentrations of macrophage inflammatory protein- beta (MIP-1α, p=0.047) and low median concentration of the stem cell growth factor beta (SCGF-β, p=0.038) compared to those without PSA. Conclusion: A degree of discordance between self-reports of consistent condom use and PSA positivity was observed. There was also evidence of a relationship between recent semen exposure, BV prevalence and altered cytokine concentrations. These findings suggest that PSA, as a semen biomarker, should be taken into consideration when investigating biological markers in the female genital tract and self-reported condom use in studies on reproductive and sexual health.